2008
DOI: 10.1016/j.ccr.2008.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The Signaling Adaptor p62 Is an Important NF-κB Mediator in Tumorigenesis

Abstract: The balance between cell death and survival, two critical aspects of oncogenic transformation, determines the outcome of tumorigenesis. Nuclear factor-kappaB (NF-kappaB) is a critical regulator of survival; it is induced by the oncogene Ras and, when inhibited, accounts for the cell death response of Ras-transformed cells. Here, we show that the signaling adaptor p62 is induced by Ras, its levels are increased in human tumors, and it is required for Ras-induced survival and transformation. p62-/- mice are resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

32
524
4
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 508 publications
(564 citation statements)
references
References 47 publications
32
524
4
4
Order By: Relevance
“…24 p62/SQSTM1 can be activated by TLR signals to ubiquitinate TRAF6 and facilitate NF-kB activation. 25 However, our results suggest that p62/SQSTM1 can terminate TLR2-induced NF-kB activity by triggering selective autophagy as a feedback regulation on NF-kB. This is the first report to demonstrate that the activity of a transcription factor can be directly regulated by selective autophagy.…”
Section: Discussionmentioning
confidence: 55%
“…24 p62/SQSTM1 can be activated by TLR signals to ubiquitinate TRAF6 and facilitate NF-kB activation. 25 However, our results suggest that p62/SQSTM1 can terminate TLR2-induced NF-kB activity by triggering selective autophagy as a feedback regulation on NF-kB. This is the first report to demonstrate that the activity of a transcription factor can be directly regulated by selective autophagy.…”
Section: Discussionmentioning
confidence: 55%
“…40 Interestingly, the activity of NF-kB is, in turn, regulated by p62/SQSTM1. 1,3,4,47 This suggests that NF-kB-mediated p62/SQSTM1 upregulation may represent a feed-forward signal for prolongation of NF-kB activity and thus cell survival during granulocytic maturation. In line with this assumption, Ling et al 51 showed that the NF-kB pathway is activated by Kras (G12D) in pancreatic ductal adenocarcinoma through p62/SQSTM1 and IL-1 alpha feed-forward loops.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Through its multi-domain structure, p62/SQSTM1 interacts specifically with key signaling proteins, including atypical PKC family members, NF-kB, and mTOR to control cellular responses. [3][4][5][6][7] p62/SQSTM1 functions also as a key mediator of autophagy. Through its interaction with LC3, an essential protein involved in autophagy, p62/SQSTM1 selectively directs ubiquitinated substrates to autophagosomes leading to their subsequent degradation in lysosomes.…”
mentioning
confidence: 99%
“…7 One of the most-studied functions of p62 is its role in regulating NF-kB activation; p62 recruits TRAF6, which then initiates NF-kB signaling. An essential role of p62 in TRAF6/NF-kB activation has been described in solid tumors, 8 and also recently in the survival of AML cells during all-trans retinoic acidinduced differentiation. 9 Given that concomitant loss of miR-146a and overexpression of p62 cooperate to enhance TRAF6/NF-kB signaling by derepressing and activating TRAF6, respectively, we hypothesize that del(5q) MDS/AML cells are vulnerable to disruption of the p62-TRAF6 complex.…”
Section: Myelodysplastic Syndromes (Mds)mentioning
confidence: 93%